Development status and development trend of smart grid - Feng, Tianyu (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
In recent years, as the world gradually enters modern industrial society, the use of electric energy has become frequent, making people's daily lives change dramatically, especially the development of the electric power industry, which is inseparable from the support of electric power system. And the traditional power supply network has been unable to meet the power supply needs of industrial society, so the smart grid came into being and became the mainstream power system. This paper introduces the definition and advantages of smart grids over traditional grids, the background and current status of smart grid development in China and the US, the current challenges facing smart grids and the technologies used to address these challenges.